Sustainable land use and its assessment: global trends - Butenko, E.; Loshakova, Y. (Land Management, Cadastre and Land Monitoring, 2020)
Sustainable land use is a necessary building block for the sustainable development of agriculture, and it is a key component of sustainable development goals, an essential condition for improving environmental, economic and social opportunities for the benefit of present and future generations, while maintaining and improving the quality of land resources. The article investigates the historical development and assesment of sustainable land uses, which serves to increase the effectiveness of decision-making on land management. The conceptual terminology and tools for assessing sustainable land use in the process of land and landscape management at national, subnational and local levels are analyzed. It provides an analysis of the main elements and sub-elements of any sustainable development program, regardless of its reference point: region, community or country. It is proposed to improve the concept of "sustainable land use" in the context of the examined inverstigated world tendencies of the paradigm of sustainable development of territories adapted to the realities of Ukraine. Keywords:sustainable development, spatial formation of land use, sustainable use, assessment.